RIGHTS AS TRUMPS, JUDICIAL ACTIVISM AND HUMAN DIGNITY IN LIGHT OF DWORKIN’S POLITICAL PHILOSOPHY - Martins, Luciano Jesus Hage (Seven Editora, 2026)
This research aims to understand, through Dworkin’s political theory of rights as trumps, the concepts of human dignity and judicial activism. According to the theory under study, rights as trumps seek to protect individuals from unjust public policies of the government, which can harm the equal distribution of rights. In this context, the study explores the concept of rights as trumps in order to understand human dignity and the counter-majoritarian role of the judiciary, and how these concepts help in the protection of fundamental rights and the distribution of rights based on equal consideration. Regarding the methodology used in this article, discourse analysis will be employed, as the objective is to understand the discourse used in the concept of rights as trumps. Thus, at the end of the work, the results obtained during the research on the analyzed topic will be presented. DOI: https://doi.org/10.56238/sevened2026.008-085